Preparation and characterization of phase‐change material nanocapsules with amphiphilic polyurethane synthesized by 3‐allyloxy‐1, 2‐propanediol. Issue 3 (8th May 2013) - Cheng, Fangli; Wei, Yanyan; Zhang, Yingying; Wang, Fufang; Shen, Tailong; Zong, Chengzhong
ABSTRACT Amphiphilic polyurethane was synthesized with 3‐allyloxy‐1, 2‐propanediol as the chain extender, which had an unsaturated double bond for further reaction. It was proven that, with such a structure, the amphiphilic polyurethane not only had good ability for emulsifying phase change materials(PCM) but also was capable of forming a cross‐linked shell. With the amphiphilic polyurethane synthesized in this study, paraffin or methyl stearate nanocapsules in the range of 300–600 nm in size were obtained by a simple high‐speed dispersion and suspension polymerization. No extra emulsifier or dispersant was added during the preparation of the nanocapsules. Tripropylene glycol diacrylate (TPGDA) was used as a crosslinking agent for strengthening nanocapsules. The crosslinking reaction of the shell materials was investigated by the NMR technique. It was found that a network structure of shells was formed after suspension polymerization. Differential scanning calorimetry (DSC) was applied to study the phase change properties of the phase‐change material nanocapsules (PCMNs). The paraffin nanocapsule was found to have a rather high encapsulation efficiency of nearly 100%, and its latent heat was able to reach 104 J/g. Thermogravimetric analysis (TGA) was used to measure the thermal stability of the PCMNs. It was indicated that the weight loss rate of PCMN decreased after encapsulated by polyurethane shells and the weight loss above 200°C decreased after adding the crosslinking agent. All of the PCMN dispersions were found to have rather good dilution stability. Besides, the dried PCMN powder was able to be redispersed into water without any additional emulsifier. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 1879–1889, 2013